La Educación en valores en el proceso de Enseñanza Aprendizaje en los Niños y Niñas de 6to. y 7mo. Año de la Escuela de Educación Básica Municipal Pradera - Calva Briceño, Dina Isabel (2016)
This research paper entitled "Values Education in the teaching-learning process in children 6th and 7th school year Basic Education Municipal Prairie" in which is raised the following scientific problem "Poor practice values and influence in the process learning of children and Intervention Social Worker " The research was developed based on the scientific method and auxiliary as inductive, deductive and statistical methods having as object of study values education in the process of learning of children, in order to improve the practice of values in the educational community of the school of Basic Education Municipal Prairie relying on theoretical recovery and methodologically, determining causes and consequences of poor practice of values. In the development of this research work the survey technique the same that was applied to children with the aim of knowing that values practice in their daily lives, to parents in order to know where applied are based values in children to to their comprehensive training and teachers in order to know what are the causes and consequences that poor practice of values in children. . It was found that 32% of children surveyed practice the value of honesty responsibility 24%, 24% punctuality and 20% of children the value of love. According to the results of the survey of parents is concluded that 60% of parents indicate that it is in the family where values are based, 34% respond that in 5 school, 3% in the media and 3% in groups of friends. therefore it can determine that there is a small percentage who consider values should be promoted in the media and groups of friends. As for the results of the survey of teachers mostly state that the causes and consequences that poor practice of values in children are: divorces, family conflicts, migration, Permissive parents, overwork, selfishness and ignorance within the consequences are mentioned by teachers, children with self-esteem, aggressive behavior, loss of respect for teachers and low performance. Finally the proposed proposal is to design a participatory action plan to strengthen education in values in the teaching-learning process in children 6th and 7th year of the School of Basic Education Municipal Prairie, which will allow there is a better coexistence among peers and family atmosphere.